A new animal model for uterine torsion and uterine ischemia‐reperfusion studies, but not fetal hypoxia studies. Issue 3 (25th September 2018) - Dogan, Halef; Timurkaan, Necati; Saat, Nevzat; Seker, Ibrahim; Risvanli, Ali
Abstract: The aim of the present study was to develop a new animal model for use in uterine torsion, uterine ischemia‐reperfusion, and fetal hypoxia studies in rats. A total of 14 pregnant rats on their 18th‐19th gestational days were used. The animals were randomly divided into two groups: those undergoing the shame operation (group 1), and those in which a 360 uterine torsion was performed using a novel technique, which was corrected 6 hours later (group 2). Subsequently, seven female and seven male rat pups aged 1 month were separated from the mothers in each group. The female rats were monitored until puberty via measuring the vaginal apertures. The 1‐month old male rats and the female rats on reaching puberty were decapitated and histopathological tests were performed on the dissected organs, including the cerebral, visceral and genital organs. At the end of the study, no differences were observed between the groups with regard to abortions, offspring death rates and congenital abnormalities. It was observed that the time to reach puberty in female rats born from mothers with uterine torsion was longer, but the difference was statistically insignificant. No microscopic lesions were detected in the cerebral, visceral or genital organs of the offspring. Accordingly, it was concluded that offspring of mothers with the uterine torsion were not affected, at least in the short term. It was generally concluded that this animal model is appropriate for use in uterine torsion and ischemia‐reperfusion studies, but is not appropriate for fetal hypoxia studies.